KESIAPAN MAHASISWA JURUSAN PENDIDIKAN ADMINSTRASI PERKANTORAN DALAM KOMPETISI PASAR KERJA DI ERA MEA - Indri Murniawaty; Wisudani Rahmaningtyas (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2017)
Nowadays, competence mastery is highly required in order to compete in the ASEAN Economic Community (AEC) Era. The purpose of this research is to figure out the students’ understanding and readiness dealing with the ASEAN Economic Community as well as the possible encountering problems when competing in the ASEAN Economic Community Era. This research uses a descriptive-qualitative approach conducted at Economics Faculty involving respondents of office administration education department students in the academic year of 2014/2015. The data are collected through questionnaires. The research results show that based on the aspect of communication competence, students are adequately ready with the percentage of 71.46%; based on the aspect of capability competence, they are categorized into high by 64.72%; and their knowledge competence has already reached 73.14%.Keywords: Labor markets in the ASEAN Economic Community (AEC) Era, Students’ readiness, Working competence,